Work Experience, Obedience Pressure and Task Complexity on Audit Judgment - Aida, Nur (Manunggal Halim Jaya, 2021)
This study aims to examine and analyze the effect of variables work experience, obedience pressure and task complexity on audit judgment. This study involved 43 auditors and data collection using a survey method. Furthermore, the data were analyzed using descriptive statistical tests, e.g., validity and reliability tests, normality test, multicollinearity test and heteroscedasticity test, and hypothesis testing (multiple linear regression equation test, determination coefficient test, f-test and statistical t-test). Based on the research results, it is concluded that work experience has a positive and significant effect on audit judgment. The more experienced an auditor is, the greater the auditor's ability to solve any existing problems and can assist the auditor in predicting and detecting problems professionally so that the resulting audit judgment is better. Second, the pressure of obedience has a negative and significant effect on audit judgment. The more professionally an auditor conducts an audit, the better the resulting audit quality. Third, task complexity has a negative and significant effect on audit judgment. The auditor carries out the more complex the assignment, the more difficult it is to complete the tasks that must be completed, and it will reduce its performance, and the audit judgment issued will be worse.